Health Utility Estimates and Their Application to HIV Prevention in the United States: Implications for Cost-Effectiveness Modeling and Future Research Needs. Issue 2 (July 2020) - Whitham, Hilary K.; Hutchinson, Angela B.; Shrestha, Ram K.; Kuppermann, Miriam; Grund, Birgit; Shouse, R. Luke; Sansom, Stephanie L.
Objectives. Health utility estimates from the current era of HIV treatment, critical for cost-effectiveness analyses (CEA) informing HIV health policy, are limited. We examined peer-reviewed literature to assess the appropriateness of commonly referenced utilities, present previously unreported quality-of-life data from two studies, and discuss future implications for HIV-related CEA.Methods. We searched a database of cost-effectiveness analyses specific to HIV prevention efforts from 1999 to 2016 to identify the most commonly referenced sources for health utilities and to examine practices around using and reporting health utility data. Additionally, we present new utility estimates from the Centers of Disease Control and Prevention's Medical Monitoring Project (MMP) and the INSIGHT Strategies for Management of Anti-Retroviral Therapy (SMART) trial. We compare data collection time frames, sample characteristics, assessment methods, and key estimates.Results. Data collection for the most frequently cited utility estimates ranged from 1985 to 1997, predating modern HIV treatment. Reporting practices around utility weights are poor and lack details on participant characteristics, which may be important stratifying factors for CEA. More recent utility estimates derived from MMP and SMART were similar across CD4+ count strata and had a narrower range than pre–antiretroviral therapy (ART) utilities.Conclusions. Despite the widespread use of ART, cost-effectiveness analysis of HIV prevention interventions frequently apply pre-ART health utility weights. Use of utility weights reflecting the current state of the US epidemic are needed to best inform HIV research and public policy decisions. Improved practices around the selection, application, and reporting of health utility data used in HIV prevention CEA are needed to improve transparency.